Deer impact seedbanks and plant communities over 18 years of post-agricultural succession - A. Sophie Westbrook; Aleah Butler-Jones; Scott H. Morris; Max Goldman; Anurag Agrawal; Antonio DiTommaso (PLoS ONE, 2025)
White-tailed deer ( Odocoileus virginianus ) are known to alter the composition of plant communities and the course of secondary succession. We present 18 years of data from a long-term deer exclosure experiment near Ithaca, NY, USA, to evaluate seedbank dynamics and the resulting aboveground community. Seedbank data were collected annually from 2005 to 2021 through a germination assay in which 280,674 emerged seedlings were identified. Aboveground data were collected from 2019 to 2022. Across all years, deer increased Shannon-Wiener diversity of seeds germinated from the soil by 8% relative to exclosure plots but did not affect abundance or species richness. Deer altered seedbank composition but not the percentage of biennial/perennial (vs. annual) or native (vs. non-native) species in the seedbank. Deer had little effect on aboveground plant communities (total cover, diversity, percentage biennial/perennial, percentage native) in 2019 or 2022. Nonetheless, deer reduced the abundance of woody plants by 50% and only the exclosure treatment had trees exceeding 1 cm diameter at breast height after 16 years. Although seedbank and aboveground plant communities changed over the study period, there was generally no interaction between the effects of exclosure treatment and year. Overall, our findings show that deer increased seedbank diversity, altered seedbank community composition, and suppressed woody plants aboveground. These changes are likely to impact the process of secondary succession. Increased seedbank diversity might increase the feasibility of passive restoration, whereas suppression of woody plants would delay forest recovery.